Pursuing Work-Life Balance through Life Crafting: A Qualitative Study on Muslim Women with Triple Burden - Sopian, Mohamad; Hanami, Yuliana (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
This article introduces a qualitative study to explore the process of life crafting to attain work-life balance (WLB) for Muslim women as academia has a triple burden in the context of career women in Indonesia. This study uses a phenomenological approach, collecting data using semi-structured in-depth interviews, and thematic analysis as a data analysis technique. Participants are full-time employed women (academics), have families, are continuing their studies, and have professional qualifications (N = 8). The findings show the dynamics of Life Crafting that underlies the work and non-work domains that affect the attainment of work-life balance in women participants working while studying. Participants were found to understand and achieve their work-life balance differently according to their personal traits. This study contributes to current knowledge about career and life issues through the perspectives and work-life experiences of professional women in Indonesia.